Hydrolysis behavior and mechanism of AlON powders - Jianxin Xu; Dongming Li; Jian Song; Delei Du; Xu Zhang (Materials & Design, 2025)
AlON-C (∼25 μm) powders were prepared using the carbothermal reduction and nitridation (CRN) method. The powders were subsequently processed through milling to obtain AlON-M (∼1.6 μm) and AlON-F (∼456 nm). The experimental results indicated that both AlON-M and AlON-F underwent hydrolysis to form Al(OH)3, and the degree of hydrolysis was positively correlated with the specific surface area. In addition, the hydrolysis degree of different morphology regions in AlON powders, from high to low, was smooth fracture, stepped surface, and tear fracture. This variation was attributed to differences in the atomic ratios of Al, O, and N within each hydrolytic morphology. It was worth noting that AlON-C with a smaller specific surface area did not undergo hydrolysis after prolonged contact with water, which contradicts theoretical expectations. Microstructure analysis showed that AlON-C has a complete and stable crystal structure, AlON-C possesses closely resembling the ideal AlON (Al23O27N5) composition, potentially explaining its exceptional resistance to hydrolysis. This article not only enriches the understanding of the hydrolysis mechanism of AlON powders, but also provides important structural control strategies for the preparation of AlON materials with specific hydrolysis activity.